2015
DOI: 10.3389/fnins.2015.00429
|View full text |Cite
|
Sign up to set email alerts
|

Depression-like Behavior Induced by Nesfatin-1 in Rats: Involvement of Increased Immune Activation and Imbalance of Synaptic Vesicle Proteins

Abstract: Depression is a multicausal disorder and has been associated with metabolism regulation and immuno-inflammatory reaction. The anorectic molecule nesfatin-1 has recently been characterized as a potential mood regulator, but its precise effect on depression and the possible mechanisms remain unknown, especially when given peripherally. In the present study, nesfatin-1 was intraperitoneally injected to the rats and the depression-like behavior and activity of the hypothalamic-pituitary-adrenal (HPA) axis were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 50 publications
6
22
0
Order By: Relevance
“…Moreover, the elevated plasma concentrations of CRP and IL-6 in patients with major depressive disorder are reported to be positively related to the increased plasma nesfatin-1 level (Xia et al, 2018), which is an anorexigenic molecule localized widely in the brain and peripheral tissues with multiple biological activities including regulation of feeding and mood (Weibert et al, 2019). Consistently, in our previous study (Ge et al, 2015a), administration with nesfatin-1 could induce depression-like behaviors, accompanied with the increased plasma concentrations of IL-6 and CRP. Moreover, the antidepressant-like effect of ibuprofen, which is one of the common used nonsteroidal anti-inflammatory drugs (NSAIDs), has demonstrated in animal studies (Mesripour et al, 2019;Seo et al, 2019).…”
Section: Introductionsupporting
confidence: 78%
“…Moreover, the elevated plasma concentrations of CRP and IL-6 in patients with major depressive disorder are reported to be positively related to the increased plasma nesfatin-1 level (Xia et al, 2018), which is an anorexigenic molecule localized widely in the brain and peripheral tissues with multiple biological activities including regulation of feeding and mood (Weibert et al, 2019). Consistently, in our previous study (Ge et al, 2015a), administration with nesfatin-1 could induce depression-like behaviors, accompanied with the increased plasma concentrations of IL-6 and CRP. Moreover, the antidepressant-like effect of ibuprofen, which is one of the common used nonsteroidal anti-inflammatory drugs (NSAIDs), has demonstrated in animal studies (Mesripour et al, 2019;Seo et al, 2019).…”
Section: Introductionsupporting
confidence: 78%
“…After exposure to CIS, the expression of NES1-positive neurons in the PVN was significantly increased, while there was no significant difference in the expression of NES1-positive neurons in the ARC. Our observation that CIS upregulated NES1 expression in the PVN, which is correlated with depression-like conditions in rats, further confirms the pro-depressive role of NES1 (35).…”
Section: Discussionsupporting
confidence: 80%
“…Apart from the findings that Nesfatin-1 is distributed in stress-related brain regions, including the hypothalamus, and colocalized with stress-related substances,18,19 intracerebroventricular administration of Nesfatin-1 has been reported to be able to activate the hypothalamic–pituitary–adrenal (HPA) axis, the hyperactivity of which is proposed to be among the causal factors for triggering depressive episodes 20. Similarly, the results of our previous study confirmed that intraperitoneal administration of Nesfatin-1 in a single dose or chronically resulted in depression-like behavior and HPA axis hyperactivity in rats 21. Furthermore, an increased plasma concentration of Nesfatin-1 and an increased hypothalamic mRNA expression of Nesfatin-1 have been observed in animal models of depression 22.…”
Section: Introductionsupporting
confidence: 80%